MENINGKATKAN KETERAMPILAN SISWA DALAM PEMBELAJARAN DATABASE, MAIL SERVER DI SEKOLAH SMKN 9 SURAKARTA - Prakoso, Luxman Aji; Almisfalah, Abu Qosim; Kurniawan, endra Arief (Buletin Literasi Budaya Sekolah, 2020)
In improving the quality of student skills in the process of learning databases, mailserver at SMKN 9 SURAKARTA, schools not only depend on the quality of managers but also improvement of management systems and the development of students' ability to apply database concepts. Mastery of database concepts is very important in order to improve student skills and improve student creativity in developing websites and improving the quality or ability of students so they can compete in the world of work. The database is one of the important components in information systems, with the information system it will provide accurate, timely and relevant information for its users so that it can be used for decision making. Teacher strategies in improving Database skills at SMKN 9 SURAKARTA, in delivering the teacher's material, first explain and explain clearly and hatefully then give examples of outputs from the database program, so students will try to be more competitive and efficient and try to improve skills in learning databases the.